Secrecy and norm emergence in cyber-space: the US, China and Russia interaction and the governance of cyber-espionage - Harnisch, Sebastian; Zettl-Schabath, Kerstin (Democracy and security, 2023)
When and how does state interaction in cyber-space result in norm development? In this article, we contend that governments take on roles vis-á-vis both domestic and foreign audiences, often resulting in conflicts between crosscutting internal and external role expectations. To alleviate these role conflicts, governments use various secret instruments of statecraft that, in turn, shape international norm development. We theorize the nexus between domestic and foreign role play and secrecy, thereby extending the understanding of role taking in international relations to the cyber-space. We argue that whereas the role conceptions of autocratic powers China and Russia have been geared toward cyber-sovereignty of the regime vis-à-vis internal and external others, the United States, as a democratic power, has sought cyber-security for both state and non-state actors in the international realm. Trying to hide some of their cyber-operations, the interaction between China, Russia and the US has resulted in a distinct pattern of cyber-proxy use and state-based surveillance interaction that has facilitated the stabilization of illiberal cyber-espionage norms and the spread of diverging notions of information sovereignty.
Online veröffentlicht 11. Juli 2022
Gesehen am 26.04.2023